2015
DOI: 10.1089/scd.2014.0278
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Nuclease-Mediated Gene Knock-In in Bovine-Induced Pluripotent Cells

Abstract: Efficient and precise genetic engineering in livestock such as cattle holds great promise in agriculture and biomedicine. However, techniques that generate pluripotent stem cells, as well as reliable tools for gene targeting in livestock, are still inefficient, and thus not routinely used. Here, we report highly efficient gene targeting in the bovine genome using bovine pluripotent cells and clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9 nuclease. First, we generate induced pluripotent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…This shows that biPS-1 is suitable for additive and potentially for subtractive genetic modification and may be used for the production of genetically modified cattle via SCNT (Cao et al, 2012;Saito et al, 2003;Verma et al, 2012). Recently, CRISPR/Cas genome editing was shown in bovine iPSCs (Heo et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…This shows that biPS-1 is suitable for additive and potentially for subtractive genetic modification and may be used for the production of genetically modified cattle via SCNT (Cao et al, 2012;Saito et al, 2003;Verma et al, 2012). Recently, CRISPR/Cas genome editing was shown in bovine iPSCs (Heo et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…The pre-implantation embryo stage is generally not favoured for genome editing as it would most likely lead to a mosaic individual and possibly to more unforeseen and unforeseeable detrimental effects. Various studies in different animal models have demonstrated the feasibility of gene-editing in animals at the zygote stage (Yoshimi et al, 2014;Heo et al, 2015;Han et al, 2014, Kang et al, 2014. The potential of the technology to prevent the onset of a genetic disorder in mice was demonstrated by the studies of Wu et al (2013) and Long et al (2014), respectively for cataract and Duchenne muscular dystrophy.…”
Section: Gene Editing In Zygotes/pre-implantation Embryosmentioning
confidence: 99%
“…Studies using gene-editing in animals such as rats 5 , cattle 6 , sheep 7 and pigs 8 , indicate that it is possible to delete or disable genes in an embryo -a simpler process than actually correcting DNA sequences -in only some of the cells.…”
Section: Editing Toolsmentioning
confidence: 99%